Biomass-based ionic liquid corrosion inhibitor as well as preparation method and application thereof

By developing biomass-based ionic liquid corrosion inhibitor [5-HMFD-NEt3]X, the problem of limited protection effect of existing corrosion inhibitors in high-concentration acidic solutions is solved, and high-efficiency corrosion protection for low carbon steel and 304 steel is achieved, and it meets the requirements of green and environmental protection.

CN119776841APending Publication Date: 2025-04-08SHANDONG AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411974640.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing ionic liquid corrosion inhibitors provide limited protection against a variety of metal materials in high concentration acidic solutions, and rely on toxic substances, which limits their wide application.

Method used

A biomass-based ionic liquid corrosion inhibitor [5-HMFD-NEt3]X was developed, where X is iodine, chlorine or bromide ion. The corrosion inhibitor was prepared by a specific preparation method, which can effectively inhibit the corrosion of low carbon steel and 304 steel in high concentration hydrochloric acid.

Benefits of technology

The corrosion inhibitor significantly improves the corrosion protection effect of metal materials in high concentration hydrochloric acid, with corrosion inhibition efficiency up to 90.3%. The preparation method is environmentally friendly, low cost, stable performance, and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776841A_ABST
    Figure CN119776841A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of ionic liquid, and provides a biomass-based ionic liquid corrosion inhibitor as well as a preparation method and application thereof. The corrosion inhibitor is prepared from 5-hydroxymethylfurfural, corrosion of metal in a concentrated hydrochloric acid medium can be effectively inhibited, the performance is stable, and when the concentration of the corrosion inhibitor is increased to 10 mM, the polarization resistance is 9251 omega.cm < 2 >, and the highest corrosion inhibition efficiency reaches 90.3%. The corrosion inhibitor also has good storage resistance, and can be sealed and stored for 2-3 years at normal temperature without the phenomenon of aggregation or turbidity. In addition, the corrosion inhibitor also has the characteristics of small dosage, high corrosion inhibition rate, low toxicity and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ionic liquids, and particularly relates to a biomass-based ionic liquid corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] The corrosion of metal structures, equipment and components not only increases production costs and safety risks, but also has negative impacts on the environment, health and transportation, and causes economic losses due to the need to repair and replace damaged parts. In industries such as oil / gas, pulp / paper, chemical / petrochemical and power plants, acidic media are often used to improve productivity, but the corrosion problem is serious. At present, adding corrosion inhibitors is an effective means of corrosion prevention and can extend the life of metal materials. Corrosion inhibitors are divided into two categories: organic and inorganic, which reduce corrosion by forming a protective barrier on the surface of the material. Although synthetic corrosion inhibitors were once popular, their use is decreasing due to toxicity and environmental regulations. Many existing corrosion inhibitors rely on toxic chromates, molybdates, vanadates and tungstates, which limits their widespread application.

[0003] As an emerging green corrosion inhibitor, ionic liquids stand out due to their simple preparation process, low cost, high electrochemical stability and excellent adhesion on metal surfaces. It is regarded as an emerging and reliable alternative to traditional corrosion inhibitors, with the advantage of adjusting its inhibition effect by flexibly selecting different combinations of cations and anions. However, most of the existing ionic liquid corrosion inhibitors are limited to imidazolyl ionic liquids, and these corrosion inhibitors can usually only provide protection for a single metal material in a low-concentration acidic solution. This limitation restricts the widespread application of ionic liquids and hinders the further development of green and sustainable ionic liquid corrosion inhibitors. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a biomass-based ionic liquid corrosion inhibitor and a preparation method and application thereof. The biomass-based ionic liquid corrosion inhibitor can play a good corrosion inhibition role on metals in an industrial corrosion inhibition environment.

[0005] The green biomass-based ionic liquid corrosion inhibitor [5-HMFD-NEt3]X provided by the present invention has the structural formula:

[0006]

[0007] Where X - Any one selected from iodide ion, chloride ion and bromide ion.

[0008] Preferably, the corrosion inhibitor is [5-HMFD-NEt3]I, and its structural formula is:

[0009]

[0010] The preparation method of the above-mentioned corrosion inhibitor mainly comprises the following steps:

[0011] (1) adding methanol to 5-hydroxymethylfurfural, and after it is fully dissolved, adding diethylamine to react;

[0012] (2) Under an ice water bath, add NaBH4 to the material obtained in the reaction in (1) to carry out a reduction reaction;

[0013] (3) After the reduction reaction in (2) is completed, the methanol is dried by spin drying, saturated sodium chloride solution is added to quench, and then extracted three times with dichloromethane, the organic phase is collected, saturated Na2SO4 solution is added to dry and remove water, and then separated and purified to obtain an ionic liquid intermediate;

[0014] (4) Add acetonitrile to the ionic liquid intermediate obtained in (3) to dissolve it, then add alkyl halide, heat and stir under reflux, and after the reaction is completed, vacuum concentrate to remove acetonitrile, wash the product with ethyl acetate 3-5 times, and vacuum dry to obtain a corrosion inhibitor.

[0015] Preferably, in (1), the molar ratio of 5-hydroxymethylfurfural to diethylamine is 5:4-7;

[0016] The molar volume ratio of 5-hydroxymethylfurfural to methanol is 0.5 mol: (25-35) mL;

[0017] The reaction temperature is 25°C to 50°C, and the reaction time is 1h to 3h.

[0018] Preferably, the molar ratio of NaBH4 in (2) to 5-hydroxymethylfurfural in (1) is 1 to 1.5:1;

[0019] The reduction reaction temperature is 25°C to 50°C, and the reaction time is 3h to 6h.

[0020] Preferably, the volume ratio of the saturated sodium chloride solution in (3) to the methanol in (1) is 1:1; and the volume ratio of the dichloromethane to the saturated sodium chloride solution used in each extraction is 3:5.

[0021] Preferably, in (4), the alkyl halide is selected from any one of ethyl iodide, ethyl chloride and ethyl bromide;

[0022] Reflux at 80°C to 120°C for 3h to 12h, and the molar ratio of the ionic liquid intermediate to the halogenated hydrocarbon is 1:0.8-1.2.

[0023] The application of the biomass-based ionic liquid corrosion inhibitor provided in the present invention in inhibiting the corrosion of metals in concentrated hydrochloric acid media is also the key protection content of this patent.

[0024] Preferably, the metal is: low carbon steel, stainless steel.

[0025] Among them, low carbon steel is a conventional carbon steel with a carbon content of less than 0.25%, and is further selected from any one of Q195 steel, Q215 steel, Q235 steel, Q255 steel, and Q275 steel.

[0026] Preferably, the stainless steel is selected from any one of 201 steel, 202 steel, 301 steel, 304 steel, 316 steel and 400 series.

[0027] Preferably, the concentration of concentrated hydrochloric acid is 1.5-2.5M.

[0028] Compared with the prior art, the present invention has the following advantages and effects:

[0029] (1) The cation groups obtained by the corrosion inhibitor provided by the present invention include potential active adsorption sites such as carbon-carbon double bonds and nitrogen atoms, and the anion iodine ion has specific adsorption characteristics. This characteristic enables the biomass ionic liquid to have a good corrosion inhibition effect on low-carbon steel and 304 steel in high-concentration hydrochloric acid. It has stable performance and is resistant to storage. It can be sealed and stored at room temperature for 2 to 3 years without aggregation or turbidity. For example, the experimental results in the embodiments of the present invention show that in the 2 mol / L hydrochloric acid blank group, the polarization resistance can be obtained by fitting the circuit to be 897.7Ω〃cm 2 When the concentration of [5-HMFD-NEt3]I was 1 mM, the polarization resistance was 3754 Ω 〃 cm 2 It was found that its corrosion inhibition efficiency could reach 76.1%; when the IL concentration increased to 10mM, the polarization resistance was 9251Ω〃cm 2 , the corrosion inhibition efficiency can reach up to 90.3%;

[0030] (2) The preparation method of the ionic liquid corrosion inhibitor mentioned in the present invention is simple, environmentally friendly and has low production cost;

[0031] (3) 5-Hydroxymethylfurfural, the raw material for preparing the corrosion inhibitor in the present invention, is a cheap, readily available, green and sustainable biomass monomer, which not only has good biosolubility, but also has the characteristics of low toxicity and easy degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Flowchart of Embodiment 1-3 of the present invention;

[0033] Figure 2 is the ionic liquid in Example 1 1 H NMR spectrum;

[0034] Figure 3 The Nyquist plot of low carbon steel at 298K in Example 2 in a 2 mol / L hydrochloric acid solution containing different concentrations of [5-HMFD-NEt3]I prepared in Example 1;

[0035] Figure 4 The potentiodynamic polarization curve of low carbon steel at 298K in Example 2 in a 2 mol / L hydrochloric acid solution containing different concentrations of [5-HMFD-NEt3]I prepared in Example 1;

[0036] Figure 5 The Nyquist plot of 304 steel at 298K in Example 2 in a 2 mol / L hydrochloric acid solution containing different concentrations of [5-HMFD-NEt3]I prepared in Example 1;

[0037] Figure 6 This is a potentiodynamic polarization curve diagram of 304 steel at 298K in Example 2 in a 2 mol / L hydrochloric acid solution containing different concentrations of [5-HMFD-NEt3]I prepared in Example 1. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in conjunction with specific implementation methods.

[0039] Example 1

[0040] The biomass-based ionic liquid corrosion inhibitor is mainly prepared by the following steps:

[0041] (1) Add 0.5 mol of 5-hydroxymethylfurfural to a 100 mL eggplant-shaped bottle, dissolve it in 30 mL of methanol, then add 0.6 mol of diethylamine and react at 25°C to 50°C for 1 h to 3 h;

[0042] (2) Under an ice water bath, add NaBH4 to the material obtained in the reaction (1), the amount of which is 1.2 times the amount of 5-hydroxymethylfurfural, and carry out a reduction reaction at 25° C. to 50° C. for 3 h to 6 h;

[0043] (3) After the reaction, the methanol was dried by spin drying, 25 mL of saturated NaCl solution was added to quench, and then extracted and washed three times with 45 mL of dichloromethane, using 15 mL of dichloromethane each time, and the organic phase was collected, 8 g of saturated Na2SO4 solution was added to dry and remove water, and then separated and purified by silica gel column chromatography to obtain an ionic liquid intermediate;

[0044] (4) The ionic liquid intermediate was added to an eggplant-shaped bottle, and then 30 mL of acetonitrile was added to dissolve it. Then, iodoethane in an amount equal to that of the ionic liquid intermediate was added, and the mixture was heated to 80 ° C and stirred under reflux for 3 h. After the reaction was completed, the acetonitrile was concentrated under a vacuum of 0.1 MPa to remove the acetonitrile. The product was washed with ethyl acetate for 4 times, and dried by heating at 47 ° C for 1 h under a vacuum of 0.1 MPa to obtain the final biomass-based ionic liquid corrosion inhibitor.

[0045] The biomass-based ionic liquid corrosion inhibitor obtained in this example was characterized by nuclear magnetic resonance, and the results were as follows: Figure 2 As shown, the molecular formula of the above biomass-based ionic liquid corrosion inhibitor is [5-HMFD-NEt3]I, and its molecular structure is:

[0046]

[0047] The specific NMR data are as follows: 1 H NMR (400MHz, D2O) δ6.74(d,J=3.3Hz,1H),6.45(d,J=3.3Hz,1H),4.55(s,2H),4.44(s,2H),3.23(q,J=7.2Hz,6H),1.33(t,J=7.2Hz,9H). 13 CNMR(101MHz,D2O)δ156.24,142.03,117.13,109.55,55.69,52.67,52.56,6.93.

[0048] Example 2

[0049] The biomass-based ionic liquid corrosion inhibitor is mainly prepared by the following steps:

[0050] (1) Add 0.5 mol of 5-hydroxymethylfurfural to a 100 mL eggplant-shaped bottle, dissolve it in 25 mL of methanol, then add 0.4 mol of diethylamine and react at 25 °C for 3 h;

[0051] (2) Add 0.5 mol NaBH4 to the material obtained in step (1) under an ice water bath, and carry out a reduction reaction at 25°C for 6 h;

[0052] (3) After the reaction, the methanol was dried by spin drying, 25 mL of saturated NaCl solution was added to quench, and then extracted and washed three times with 45 mL of dichloromethane, using 15 mL of dichloromethane each time, and the organic phase was collected, 8 g of saturated Na2SO4 solution was added to dry and remove water, and then separated and purified by silica gel column chromatography to obtain an ionic liquid intermediate;

[0053] (4) The ionic liquid intermediate was added to an eggplant-shaped bottle, and then 30 mL of acetonitrile was added to dissolve it, and then ethyl chloride in an amount equal to that of the ionic liquid intermediate was added, and the mixture was heated to 120°C and stirred under reflux for 3 h. After the reaction was completed, the acetonitrile was removed by concentration under a vacuum of 0.1 MPa, and the product was washed with ethyl acetate for 3 times, and dried by heating at 47°C for 1 h under a vacuum of 0.1 MPa to obtain the final biomass-based ionic liquid corrosion inhibitor. The molecular formula of the above-mentioned biomass-based ionic liquid corrosion inhibitor is [5-HMFD-NEt3]Cl.

[0054] Example 3

[0055] The biomass-based ionic liquid corrosion inhibitor is mainly prepared by the following steps:

[0056] (1) Add 0.5 mol of 5-hydroxymethylfurfural to a 100 mL eggplant-shaped bottle, dissolve it in 35 mL of methanol, then add 0.7 mol of diethylamine and react at 50°C for 3 h;

[0057] (2) Under an ice water bath, add NaBH4 to the material obtained in the reaction (1), the amount of which is 1.5 times the amount of 5-hydroxymethylfurfural, and carry out a reduction reaction at 50° C. for 3 h;

[0058] (3) After the reaction, the methanol was dried by spin drying, 25 mL of saturated NaCl solution was added to quench, and then extracted and washed three times with 45 mL of dichloromethane, using 15 mL of dichloromethane each time, and the organic phase was collected, 8 g of saturated Na2SO4 solution was added to dry and remove water, and then separated and purified by silica gel column chromatography to obtain an ionic liquid intermediate;

[0059] (4) The ionic liquid intermediate was added to an eggplant-shaped bottle, and then 30 mL of acetonitrile was added to dissolve it, and then ethyl bromide in an amount equal to that of the ionic liquid intermediate was added, and the mixture was heated to 120°C and stirred under reflux for 12 hours. After the reaction was completed, the acetonitrile was concentrated under a vacuum of 0.1 MPa to remove the acetonitrile, and the product was washed with ethyl acetate for 5 times, and dried at 47°C under a vacuum of 0.1 MPa for 1 hour to obtain the final biomass-based ionic liquid corrosion inhibitor. The molecular formula of the above-mentioned biomass-based ionic liquid corrosion inhibitor is [5-HMFD-NEt3]Br.

[0060] Test Example: Corrosion inhibition test of low carbon steel and 304 steel in concentrated hydrochloric acid medium

[0061] In order to demonstrate the corrosion inhibition effect of the biomass-based ionic liquid corrosion inhibitor ([5-HFMD-NEt3]I) obtained in Example 1 on two metal materials (mild steel and 304 steel) in high concentration hydrochloric acid (concentration of 2M), the inventors designed six inhibition test systems for mild steel and 304 steel as inhibition test systems, respectively. The concentrations of [5-HFMD-NEt3]I in the six systems were 0, 1mM, 2.5mM, 5mM, 7.5mM, and 10mM, respectively; the concentration of hydrochloric acid was 2M, and the other test conditions were the same. After each test, the surfaces of mild steel and 304 steel (working electrode) were polished with 3000 mesh and 2000 mesh sandpaper, respectively, and recycled for the next test.

[0062] 2.1 Electrochemical testing

[0063] Electrochemical tests were carried out on the above six systems respectively. The electrochemical workstation model used for the electrochemical tests was CHI660E. The experiment adopted a traditional three-electrode system, in which the working electrode (WE) was the above-mentioned low-carbon steel and 304 steel, and the test area was 1cm 2 , the reference electrode (RE) is a mercurous sulfate electrode, and the counter electrode (CE) is a platinum sheet.

[0064] Working electrode pretreatment: Before each test, the surface of low carbon steel and 304 steel was polished with 5000#, 1000#, 1500#, and 2000# sandpaper in turn, and then washed in distilled water and anhydrous ethanol in turn, dried with cold air, and then dried at room temperature.

[0065] Experimental process parameter setting:

[0066] (1) Under constant temperature conditions of 298K, the working electrode was immersed in the above inhibition test system for 30 min, and an open circuit potential test was performed to make the OCP reach a stable value.

[0067] (2) After the open circuit potential is stabilized, the electrochemical impedance spectroscopy (EIS) test and the potentiodynamic polarization curve (PD) test are performed respectively;

[0068] The electrochemical impedance spectroscopy (EIS) test was performed with a 5mV voltage applied and a frequency range of 10kHz to 10 -2 Hz sinusoidal alternating current;

[0069] In the potentiodynamic polarization (PD) test, the scan rate was 1 mV / s and the potential range was ±250 mV relative to the open circuit potential.

[0070] (3) The corresponding electrochemical impedance spectroscopy (EIS) data were fitted using Zview 2.0 software. max and n, C can be calculated by the following formula dl (Dual Capacitor):

[0071] C dl =CPE×(2πf max ) n-1

[0072] Where n is the coefficient of the impedance arc, f max The frequency corresponding to the maximum value of the imaginary part of the impedance in the Nyquist diagram. The corrosion inhibition efficiency η obtained by the EIS experiment can be calculated using the following relationship p (%):

[0073]

[0074] In the formula, R P(inh) and R pThese are the polarization resistances with and without adding corrosion inhibitor, respectively.

[0075] (4) Corrosion potential (E corr ), corrosion current density (i corr ), the anode and cathode Tafel slopes (β a and β c ) and other kinetic parameters. The corrosion inhibition efficiency η can be calculated by the following relationship p (%):

[0076]

[0077] In the above formula, i corr is the corrosion current density without adding corrosion inhibitor, i corr(inh) is the corrosion current density with added corrosion inhibitor.

[0078] 2.2 Analysis of results of mild steel-2M HCl solution system

[0079] It is known that the concentration of hydrochloric acid in the system is 2 mol / L

[0080] Table 1 Nyquist electrochemical parameters of low carbon steel in 2 mol / L HCl solution containing different concentrations of [5-HMFD-NEt3]I at 298 K

[0081]

[0082] In Table 1, R s is the solution resistance; R ct is the polarization resistance; CPE is the constant phase element; n is the coefficient of the impedance arc; η p is the corrosion inhibition efficiency obtained from the EIS experiment.

[0083] Figure 3 Combined with Table 1, it can be seen that in the blank group (Black group), the polarization resistance can be obtained by fitting the circuit to be 11.34Ω·cm 2 ;

[0084] When the addition concentration of [5-HMFD-NEt3]I is 1 mM, the polarization resistance is 32.60 Ω·cm 2 , and found that its corrosion inhibition efficiency can reach 65.2%;

[0085] When the IL concentration increased to 10 mM, the polarization resistance was 254.00 Ω·cm 2 The corrosion inhibition efficiency can reach up to 95.5%.

[0086] The reason is analyzed as follows: In a 2mol / L hydrochloric acid solution system, the Nyquist plots with different [5-HMFD-NEt3]I concentrations are composed of capacitive reactance arcs in the high-frequency region. Due to the uneven surface of mild steel, the Nyquist plot in the blank solution presents a slightly compressed semicircle. With the increase of the corrosion inhibitor concentration, the radius of the capacitive reactance arc increases significantly. This is because [5-HMFD-NEt3]I forms a protective film on the surface of mild steel. With the increase of the corrosion inhibitor concentration, the protective film can be made denser, thereby improving the corrosion inhibition efficiency and achieving a better corrosion inhibition effect.

[0087] Table 2 Polarization curve parameters of low carbon steel in 2 mol / L HCl solution containing different concentrations of [5-HMFD-NEt3]I at 298 K

[0088]

[0089] Table 2 E corr represents the corrosion potential, i corr represents the corrosion current density, η p Represents the corrosion inhibition efficiency. c and β α are the cathode slope and anode slope obtained by extrapolation, respectively.

[0090] 2.3 Analysis of results of 304 steel-2M HCl solution system

[0091] Table 3 Nyquist electrochemical parameters of 304 steel in 2 mol / L HCl solution containing different concentrations of [5-HMFD-NEt3]I at 298 K

[0092]

[0093] Table 4 Polarization curve parameters of 304 steel in 2 mol / L HCl solution containing different concentrations of [5-HMFD-NEt3]I at 298 K

[0094]

[0095] Table 4 E corr represents the corrosion potential, i corr represents the corrosion current density, η p Represents the corrosion inhibition efficiency. c and β α are the cathode slope and anode slope obtained by extrapolation, respectively.

[0096] Combination of Table 3 and Table 4 Figure 5 As shown in the 2 mol / L hydrochloric acid blank group, the polarization resistance can be obtained by fitting the circuit to be 897.7Ω·cm 2; When the addition concentration of [5-HMFD-NEt3]I is 1mM, the polarization resistance is 3754Ω·cm 2 It was found that its corrosion inhibition efficiency could reach 76.1%; when the IL concentration increased to 10mM, the polarization resistance was 9251Ω·cm 2 , the highest corrosion inhibition efficiency reached 90.3%. In a 2mol / L hydrochloric acid solution system, the Nyquist plots with different [5-HMFD-NEt3]I concentrations consisted of a capacitive reactance arc in the high-frequency region and an inductive reactance arc in the low-frequency region. Due to the uneven surface of 304 steel, the Nyquist plot in the blank solution showed a slightly compressed semicircle. With the increase of the corrosion inhibitor concentration, the radius of the capacitive reactance arc increased significantly, which was due to the formation of a protective film by [5-HMFD-NEt3]I on the surface of 304 steel, which inhibited corrosion.

[0097] In summary, the corrosion inhibitor provided by the present invention is prepared from 5-hydroxymethylfurfural, can effectively inhibit the corrosion of low-carbon steel and stainless steel in concentrated hydrochloric acid medium, and has stable performance and storage resistance. It can be sealed and stored for 2 to 3 years at room temperature without aggregation or turbidity.

[0098] According to the characteristics and working principle of the corrosion inhibitor in this application, in addition to the low carbon steel and 304 steel listed in this application, it also has a corrosion inhibition effect on other metals in concentrated acid. Such conversion of metals also falls within the protection scope of this application. Similarly, the concentrated acid can be concentrated hydrochloric acid, or concentrated sulfuric acid, or concentrated nitric acid and other inorganic acids or organic acids.

[0099] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent changes and modifications made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. Biomass-based ionic liquid corrosion inhibitor, characterized in that: The corrosion inhibitor is [5-HMFD-NEt3]X, and its structural formula is: Among them, X - Any one selected from iodide ion, chloride ion and bromide ion.

2. The method for preparing the biomass-based ionic liquid corrosion inhibitor according to claim 1, mainly comprising the following steps: (1) adding methanol to 5-hydroxymethylfurfural, and after it is fully dissolved, adding diethylamine to react; (2) Under an ice water bath, add NaBH4 to the material obtained in the reaction in (1) to carry out a reduction reaction; (3) After the reduction reaction in (2) is completed, the methanol is dried by spin drying, saturated sodium chloride solution is added to quench, and then extracted three times with dichloromethane, the organic phase is collected, saturated Na2SO4 solution is added to dry and remove water, and then separated and purified to obtain an ionic liquid intermediate; (4) Add acetonitrile to the ionic liquid intermediate obtained in (3) to dissolve it, then add alkyl halide, heat and stir under reflux, and after the reaction is completed, vacuum concentrate to remove acetonitrile, wash the product with ethyl acetate 3-5 times, and vacuum dry to obtain a corrosion inhibitor.

3. The preparation method according to claim 2, characterized in that: (1), the molar ratio of 5-hydroxymethylfurfural to diethylamine is 5:4-7; The molar volume ratio of 5-hydroxymethylfurfural to methanol is 0.5 mol: (25-35) mL; the reaction temperature is 25° C.-50° C., and the reaction time is 1 h-3 h.

4. The preparation method according to claim 2, characterized in that: The molar ratio of NaBH4 in (2) to 5-hydroxymethylfurfural in (1) is 1 to 1.5:1; During the reduction reaction, the temperature is 25°C to 50°C and the reaction time is 3h to 6h.

5. The preparation method according to claim 2, characterized in that: The volume ratio of the saturated sodium chloride solution in (3) to the methanol in (1) is 1:1; The volume ratio of dichloromethane to saturated sodium chloride solution used in each extraction was 3:

5.

6. The preparation method according to claim 2, characterized in that: (4), the alkyl halide is selected from any one of ethyl iodide, ethyl chloride, and ethyl bromide; Reflux at 80°C to 120°C for 3h to 12h, and the molar ratio of the ionic liquid intermediate to the halogenated hydrocarbon is 1:0.8-1.

2.

7. The use of the biomass-based ionic liquid corrosion inhibitor as claimed in claim 1 in inhibiting metal corrosion in a concentrated hydrochloric acid medium, characterized in that: The metals are: low carbon steel and stainless steel.

8. The use according to claim 7, characterized in that The concentration of the concentrated hydrochloric acid is 1.5-2.5M.

9. The use according to claim 7, characterized in that The low carbon steel is selected from any one of Q195 steel, Q215 steel, Q235 steel, Q255 steel and Q275 steel; The stainless steel is selected from any one of 201 steel, 202 steel, 301 steel, 304 steel, 316 steel and 400 series.